Metabolomics for Agricultural Waste Valorization: Shifting Toward a Sustainable Bioeconomy - Khaksar, Gholamreza; Sirijan, Mongkon; Suntichaikamolkul, Nithiwat; Sirikantaramas, Supaart (Frontiers in Plant Science, 2022)
Agriculture has been considered as a fundamental industry for human survival since ancient times. Local and traditional agriculture are based on circular sustainability models, which produce practically no waste. However, owing to population growth and current market demands, modern agriculture is based on linear and large-scale production systems, generating tons of organic agricultural waste (OAW), such as rejected or inedible plant tissues (shells, peels, stalks, etc.). Generally, this waste accumulates in landfills and creates negative environmental impacts. The plant kingdom is rich in metabolic diversity, harboring over 200,000 structurally distinct metabolites that are naturally present in plants. Hence, OAW is considered to be a rich source of bioactive compounds, including phenolic compounds and secondary metabolites, that exert a wide range of health benefits. Accordingly, OAW can be used as extraction material for the discovery and recovery of novel functional compounds that can be reinserted into the production system. This approach would alleviate the undesired environmental impacts of OAW accumulation in landfills, while providing added value to food, pharmaceutical, cosmetic, and nutraceutical products and introducing a circular economic model in the modern agricultural industry. In this regard, metabolomics-based approaches have gained increasing interest in the agri-food sector for a variety of applications, including the rediscovery of bioactive compounds, owing to advances in analytical instrumentation and data analytics platforms. This mini review summarizes the major aspects regarding the identification of novel bioactive compounds from agricultural waste, focusing on metabolomics as the main tool.